Evolutionary Selection against Iteratively Weakly Dominated Strategies - Axel Bernergård; Erik Mohlin (Lund University, School of Economics and Management, Department of Economics, 2018)
This paper provides sufficient conditions under which convex monotonic evolutionary dynamics (a class of imitative dynamics that includes the replicator dynamic) select against strategies that do not survive iterated elimination of weakly dominated strategies. We apply these conditions to Bertrand duopolies, first-price auctions, finitely repeated Prisoner's Dilemmas, and the p-Beauty Contests. Our conditions also imply evolutionary selection against all iteratively strictly dominated strategies.
Keywords: C72; C73; 330; Iterated elimination of weakly dominated strategies; Iterated admissibility; Payoff monotonicity; Convex monotonicity; Evolutionary dynamics; Replicator dynamic